PNEUMOTHORAX IN A NEWBORN WITH MECONIUM ASPIRATION SYNDROME : A Case Report (Cuestiones de Fisioterapia, 2025)
Pneumothorax is the dissection of air into the pleural space. MAS has become 20% cause of pneumothorax. The thick, viscid meconium can result in partial airway obstruction with air-leak syndrome as the complication. We found respiratory distressin this baby who born through meconium-stained amniotic fluid (MSAF). The risk factor of this case was amniotic membrane rupture 3 days before delivery, oligohydramnion and preeclamsic mother . During the observation, the baby becamemore cyanotic and respiratory distress. Chest X-Ray examination revealed avascular lucent area at right lateral hemithorax, as a sign of pneumothorax. The baby got chest tube insertion and intubated with oxygen support ventilator. The serial thorax x-ray evaluation showed improvement of lung expansion, without air leakage in right pleural. After 7 days, the chest tube was taken off.